Fetal Tissue Research and the Misread Compromise - Kearney, Warren (The Hastings Center report, 1991)
The bill to restore federal funding for human fetal tissue research has been passed by the House and awaits Senate approval. But it requires women who are willing to donate fetal tissue to certify that they did not have an abortion with the intent to donate. It further requires researchers to keep the certifications on file and available for government audit. Both requirements spell trouble.